Nitrogen uptake kinetics of an enteric methane inhibitor, the red seaweed Asparagopsis armata - Torres, Raquel (2022)
The use of red seaweeds of the genus Asparagopsis as a feed ingredient drastically decreases the enteric methane production by ruminant livestock, thereby reducing the environmental impact of this industry. To address the world demand for Asparagopsis mass production, it is essential to understand the species nutrition. In this study, we evaluated for the first time the uptake kinetics of inorganic and organic nitrogen forms of the tetrasporophyte of Asparagopsis armata, to identify the different uptake phases (surge and internally controlled) and to reveal the species preferential nitrogen sources. The time course of nitrogen uptake rates was followed, and the preferential nitrogen sources were assessed in choice-uptake experiments through the incorporation of (15) N-labelled ammonium, nitrate and amino acids. As expected, the short-term, surge uptake rates were much higher than the stabilized internally controlled uptake rates. Ammonium was the preferred form during the internally controlled phase but surprisingly, the surge uptake rates of amino acids were much higher than those of inorganic forms. The importance of amino acids for A. armata nutrition was further supported by its internally controlled uptake rates that where higher than those of nitrate. Ammonium is, thus, the main nitrogen form for the species nutrition, but pulses of organic nitrogen may be considered in the mass production of Asparagopsis for the enteric methane inhibition of the livestock industry.